Enhanced methane production from waste activated sludge by combining calcium peroxide with ultrasonic: Performance, mechanism, and implication. (May 2019) - Li, Xiaoming; Liu, Yu; Xu, Qiuxiang; Liu, Xuran; Huang, Xiaoding; Yang, Jingnan; Wang, Dongbo; Wang, Qilin; Liu, Yiwen; Yang, Qi
Graphical abstract: Highlights: CaO2 + ultrasonic synergistically improved the intensity of free radicals. CaO2 + ultrasonic facilitated solubilization and release of biodegradable organics. CaO2 + ultrasonic improved the hydrolysis rate and biochemical methane potential. CaO2 + ultrasonic enhanced the removal of refractory organic pollutants. Abstract: This study reported a novel and high-efficient pretreatment method for anaerobic digestion, i.e., combining calcium peroxide (CaO2 ) with ultrasonic (US), by which not only the methane production was remarkably improved but also the removal of refractory organic contaminants was enhanced. Experimental results showed the optimum condition for methane production was achieved at 0.1 g CaO2 /g VSS combined with US (1 W/ml, 10 min). Under this condition, the maximal methane yield of 211.90 ± 2.6 L CH4 /kg VSS was obtained after 36 d of anaerobic digestion, which was respectively 1.36-fold, 1.19-fold and 1.26-fold of that from the control, solo US (1 W/ml, 10 min) and solo CaO2 (0.1 g/g VSS). Mechanism investigations revealed that CaO2 + US not only improved the disintegration of waste activated sludge (WAS) but also increased the proportion of biodegradable organic matters. Moreover, the total frequency of recalcitrant contaminants contained in WAS decreased significantly when CaO2 + US was applied.